A decade of the International Journal of Entrepreneurship and Small Business: a bibliometric analysis. (2018) - Laudano, Maria Carmen; Marzi, Giacomo; Caputo, Andrea
The purpose of this paper is to offer a complete overview of the International Journal of Entrepreneurship and Small Business ( IJESB ). By using Scopus and Google Scholar databases to analyse the most cited papers and the most prolific authors, the article provides a map of the knowledge produced and disseminated by IJESB taking 809 papers into consideration. Furthermore, through keywords correlation analysis, the authors highlight the most relevant topics and the relative importance in terms of number of citations, by analysing how they are clustered together. Finally, the paper shows the past, the present, and the future trends in IJESB through a representation of the average emergence date of each keyword.